The Constant Switching Frequency And Torque Ripple Reduction Of Direct Torque Controlled Induction Machine With Neutral Point Clamped Inverter - Ismail, Huzainirah (2018)
Direct Torque Control (DTC) of induction motor drives are widely accepted in variable speed drive applications because it offers high performance in terms of fast torque response as well as simplicity of control structure. However, conventional OTC drives which utilize two-level inverter and hysteresis controllers inherently suffer from two major drawbacks which are large torque ripple and variable switching frequency particularly at low speed operation. This is because the torque is unable to restricted within the hysteresis band (commonly happened in digital implementation of hysteresis controller) that leads to condition of overshoot and undershoot which result in large torque ripple. Secondly, inappropriate selection of voltage vectors for different speed operation as two-level inverter provides only limited numbers of voltage vectors. This research aims to improve the performance of the OTC drives by utilizing a three-level Neutral Point Clamped (NPC) inverter as appropriate voltage vectors can be utilized for different speed operations due to availability of larger number of voltage vectors . Nevertheless, the utilisation of NPC inverter lead to imbalance of upper and lower capacitor voltage due to application of short amplitude of voltage vectors which have two redundant switching states and each switching state produces different effect towards the capacitor voltage. Therefore, a simple capacitor voltage balancing strategy is also proposed to select the appropriate switching states based on capacitor voltage status. Next, the selection of appropriate voltage vectors according to speed operation are determined to produce reduction of torque ripple and switching frequency. Furthermore, a constant switching frequency operation is obtained by replacing the hysteresis torque controller with constant switching frequency (CSF) torque controller. The proposed improvement method was conducted experimentally using DTC-N PC inverter drives with CSF torque controller (with acronym DTC-N PC-CSF) and was compared with conventional OTC drives as well as OTC drives with N PC inverter and hysteresis torque controller (with acronym DTC-NPC-HTC) for performance analysis. The performance result showed that the torque ripple was minimized and the switching frequency was remained constant for all range of speeds.